GRATIFIKASI DI MAHKAMAH KONSTITUSI DAN WACANA HUKUMAN MATI - Irfan, M. Nurul (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2014)
Gratification in The Constitutional Court and Discourse of Death Penalty. The gratification case doneby an ex-governor and an ex-judge of The Constitutional Court is very irony. As the last gate guard in lowenforcement, the Court which concerns in struggling justice has “fallen off” due to greasing the palm done bythe ex-chief judge. In view of Islamic perspective, the gratification crime belongs to jarîmah ta’zîr, a punishmentrelates to the policy of local government. It does not belong to jarîmah qishâs or hudûd which the punishmentis determinated by the Qur’an and hadîts. Hence, there is discourse of death penalty for the gratification casein The Constitutional Court in order to make wary effect. It is because one of the ta’zîr punishments is deathpenalty that causes big hazard effect for all.